CD4+ T cell counts and soluble programmed death-1 at baseline correlated with hepatitis B surface antigen decline in HIV/HBV coinfection during combined antiretroviral therapy - Li, Xiaodi; Xu, Ling; Lu, Lianfeng; Liu, Xiaosheng; Yang, Yang; Wu, Yuanni; Han, Yang; Li, Xiaoxia; Li, Yanling; Song, Xiaojing; Cao, Wei; Li, Taisheng (Frontiers in Cellular and Infection Microbiology, 2023)
Background Several studies have described the rapid decline and clearance of hepatitis B surface antigen (HBsAg) in human immunodeficiency virus (HIV)/hepatitis B virus (HBV) coinfection after initiating combined antiretroviral therapy (cART). Early decline of HBsAg levels is associated with HBsAg seroclearance in the treatment of chronic HBV infection. This study aims to evaluate the HBsAg kinetics and the determinants of early decline of HBsAg in patients with HIV/HBV coinfection during cART. Methods A total of 51 patients with HIV/HBV coinfection were enrolled from a previously established HIV/AIDS cohort and followed for a median of 59.5 months after cART initiation. Biochemical tests, virology and immunology assessments were measured longitudinally. The kinetics of HBsAg during cART were analyzed. Soluble programmed death-1 (sPD-1) levels and immune activation markers (CD38 and HLA-DR) were measured at baseline, 1-year and 3-year during treatment. HBsAg response was defined as a decline of more than 0.5 log10 IU/ml at 6 months from the baseline after initiation of cART. Results The HBsAg declined faster (0.47 log10 IU/mL) in the first six months and attained a decrease of 1.39 log10 IU/mL after 5-year therapy. Seventeen (33.3%) participants achieved a decline of more than 0.5 log10 IU/ml at the first 6 months of cART(HBsAg response). Among them, five patients achieved HBsAg clearance at a median of 11 months (range: 6-51 months). Multivariate logistic analysis showed the lower baseline lower CD4+ T cell levels (OR=6.633, P=0.012) and sPD-1 level (OR=5.389, P=0.038) were independently associated with HBsAg response after cART initiation. The alanine aminotransferase abnormality rate and HLA-DR expression were significantly higher in patients who achieved an HBsAg response than in those who did not achieve an HBsAg response after cART initiation. Conclusions Lower CD4 + T cells, sPD-1, and immune activation were related to a rapid HBsAg decline in patients with HIV/HBV-coinfected after the initiation of cART. These findings imply that immune disorders induced by HIV infection may disrupt immune tolerance to HBV, leading to a faster decline in HBsAg levels during coinfection.